Enteric Neuropathy Can Be Induced by High Fat Diet In Vivo and Palmitic Acid Exposure In Vitro - Voss, Ulrikke (Public Library of Science, 2013)

(untitled)
OBJECTIVE: Obese and/or diabetic patients have elevated levels of free fatty acids and increased susceptibility to gastrointestinal symptoms. Since the enteric nervous system is pivotal in regulating gastrointestinal functions alterations or neuropathy in the enteric neurons are suspected to occur in these conditions. Lipid induced intestinal changes, in particular on enteric neurons, were investigated in vitro and in vivo using primary cell culture and a high fat diet (HFD) mouse model. DESIGN: Mice were fed normal or HFD for 6 months. Intestines were analyzed for neuronal numbers, remodeling and lipid accumulation. Co-cultures of myenteric neurons, glia and muscle cells from rat small intestine, were treated with palmitic acid (PA) (0 – 10(−3) M) and / or oleic acid (OA) (0 – 10(−3) M), with or without modulators of intracellular lipid metabolism. Analyses were by immunocyto- and histochemistry. RESULTS: HFD caused substantial loss of myenteric neurons, leaving submucous neurons unaffected, and intramuscular lipid accumulation in ileum and colon. PA exposure in vitro resulted in neuronal shrinkage, chromatin condensation and a significant and concentration-dependent decrease in neuronal survival; OA exposure was neuroprotective. Carnitine palmitoyltransferase 1 inhibition, L-carnitine- or alpha lipoic acid supplementation all counteracted PA-induced neuronal loss. PA or OA alone both caused a significant and concentration-dependent loss of muscle cells in vitro. Simultaneous exposure of PA and OA promoted survival of muscle cells and increased intramuscular lipid droplet accumulation. PA exposure transformed glia from a stellate to a rounded phenotype but had no effect on their survival. CONCLUSIONS: HFD and PA exposure are detrimental to myenteric neurons. Present results indicate excessive palmitoylcarnitine formation and exhausted L-carnitine stores leading to energy depletion, attenuated acetylcholine synthesis and oxidative stress to be main mechanisms behind PA-induced neuronal loss.High PA exposure is suggested to be a factor in causing diabetic neuropathy and gastrointestinal dysregulation.